2022
DOI: 10.1038/s41467-022-31097-7
|View full text |Cite
|
Sign up to set email alerts
|

A global lipid map reveals host dependency factors conserved across SARS-CoV-2 variants

Abstract: A comprehensive understanding of host dependency factors for SARS-CoV-2 remains elusive. Here, we map alterations in host lipids following SARS-CoV-2 infection using nontargeted lipidomics. We find that SARS-CoV-2 rewires host lipid metabolism, significantly altering hundreds of lipid species to effectively establish infection. We correlate these changes with viral protein activity by transfecting human cells with each viral protein and performing lipidomics. We find that lipid droplet plasticity is a key feat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 76 publications
4
28
0
Order By: Relevance
“…Supplementation of saturated PA and unsaturated OA and LA in the condition of FFA deficiency has been reported to restore the replication of not only RNA viruses including not only SARS-CoV-2, IAV, MERS-CoV, and enterovirus but also DNA viruses such as adenovirus. 11 , 15 In agreement with previous studies, 11 , 15 supplementation of FFAs during FFA deficiency by lipase inhibitors was found to rescue the replication of SARS-CoV-2 and IAV. The addition of unsaturated FFAs such as LA and OA at the time of virus inoculation is known to inhibit pathogenic human β-coronaviruses through their binding to FFA binding pocket in the spike protein, which blocks virus entry.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Supplementation of saturated PA and unsaturated OA and LA in the condition of FFA deficiency has been reported to restore the replication of not only RNA viruses including not only SARS-CoV-2, IAV, MERS-CoV, and enterovirus but also DNA viruses such as adenovirus. 11 , 15 In agreement with previous studies, 11 , 15 supplementation of FFAs during FFA deficiency by lipase inhibitors was found to rescue the replication of SARS-CoV-2 and IAV. The addition of unsaturated FFAs such as LA and OA at the time of virus inoculation is known to inhibit pathogenic human β-coronaviruses through their binding to FFA binding pocket in the spike protein, which blocks virus entry.…”
Section: Discussionsupporting
confidence: 89%
“…2k, l ), an observation consistent with the previous reports. 11 , 15 Furthermore, siRNA-mediated gene silencing of ATGL and/or HSL markedly suppressed the protein expression levels of hemagglutinin (HA) and M2 (active as an ion channel 16 ), genome replication, and infectious progeny production through inhibition of LD degradation in IAV-infected A549 cells (Fig. 2m–p ).…”
Section: Resultsmentioning
confidence: 93%
“… 38 Studies also suggest substantial changes in oral and gut microbiome and proteomic and metabolomic profiles of individuals infected with SARS-CoV-2 that could last well beyond the acute phase and contribute to changes in lipid profiles. 1 , 2 , 3 , 4 , 5 , 37 , 38 , 39 , 40 Behavioural changes, such as a change in diet and exercise, other COVID-19 pandemic stressors (including lockdowns, social isolation, and loneliness), grief, and other stressors might have differentially affected people with COVID-19 and could also be responsible for some of the effect seen here. We observed a higher risk of an increase in BMI in people with COVID-19 versus both the contemporary and historical controls; the extent to which this increase in BMI following SARS-CoV-2 infection might mediate incident dyslipidaemia or whether, conversely, occurrence of dyslipidaemia following infection might mediate the increase in BMI will need to be examined in future studies.…”
Section: Discussionmentioning
confidence: 89%
“…1 , 2 , 3 ). A lipidomics study has also shown that there are no differences in lipid profiles in patients infected with different virus variants (Farley et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%